SEKSUALITAS: SUATU TINJAUAN ETIS KRISTIANI TERHADAP PEMAHAMAN MAHASISWA FAKULTAS TEOLOGI UNIVERSITAS KRISTEN INDONESIA TOMOHON TENTANG HUBUNGAN SEKS - Sumeleh, Allan Rifandi (Tumou Tou, 2019)
Sexuality for some people is often considered a taboo thing to talk about but among young people this is important to know especially among students. Because in the era of openness of various information, it becomes interesting to discuss sexuality in various studies. The purpose of this study is to ethically study theological issues of sexuality in the understanding of students of the Theological Theology Faculty at the Indonesian Christian University of Tomohon by using descriptive qualitative research methods and using the theories of Malcolm Brownlee and J. L. Abineno and trying to study them in Bible view.